Non-functional requirements interdependencies in web service composition - El Kassmi, Ilyass; Jarir, Zahi; Obaid, Abdellatif (2016 Third International Conference on Systems of Collaboration (SysCo), 2016)
Web services composition has been an active area of Service-oriented computing research. Where in literature the subjects around the functional composition of web service has gained increasing attention, some other efforts have been deployed to integrate the Non-functional requirements to be taken in consideration by the web service composition. However, integrating different Non-functional requirements in a composition of web services is a highly complex task and can lead to undesirable interactions that negatively affect service quality and the expected result. In this paper we propose a Finite State Automata based approach for modeling and integrating Non-functional requirements taking in consideration their interdependencies. To validate our formalization UPPAAL model checking tool is used. In this work we applied our approach to Security as Non-functional Requirements, and proposed a Health Care case study for experimentations.